Use the Power Rule of Exponents to simplify the expression (62)4.

3 answers

To simplify the expression \((62)^4\) using the Power Rule of Exponents, we multiply the exponents.

So, we have:
\begin{align*}
(62)^4 &= 6^4 \cdot 2^4 \\
&= 1296 \cdot 16 \\
&= \boxed{20,736}
\end{align*}
Use the Power Rule of Exponents to simplify the expression (6^2)^4.
To simplify the expression \((6^2)^4\) using the Power Rule of Exponents, we multiply the exponents.

So, we have:
\begin{align*}
(6^2)^4 &= 6^{2 \cdot 4}\\
&=6^8 \\
&= \boxed{46,656}
\end{align*}